THE INFLUENCE OF AUTOVENOUS ULTRAVIOLET IRRADIATION OF BLOOD SEPARATELY AND WITH ACETYLSALICYLIC ACID ON HEMOSTASIS STATE IN PATIENTS AFTER MYOCARDIAL INFARCTION - I. N. Rjamsina; V. A. Chereshnev (Российский кардиологический журнал, 2003)
The article deals with the study of influence of autovenous ultraviolet irradiation of blood (AUIB) in monotherapy and in combination with acetylsalicylic acid on hemostasis state in patients on out-patients rehabilitation stage after myocardial infarction. 26 men were included in the study. 16 patients of the first group were underwent by 5 procedures of AUIB; 10 patients of second group combined A UIB with acetylsalicylic acid intake 250 mg daily. As the most strongly pronounced effect of AUIB was blood fibrinolytic system activation. The significant increase of soluble fibrin-monomer complex (SFMC) level was revealed that by indirection could testify to pro-thrombotic effect of method. Combined therapy by AUIB and acetylsalicylic acid resulted in increase of antiaggregant action and reduce the number of SFMC.